Potential Nephrotoxic Sequel of the Kidney Following Exposure to Turmeric Extract in Adult Wistar Rats - Ahama, Efe; Igben, Vincent-Junior Onoriode; Ubogu, Joseph; Ifechukwude, Ignatius Osakue; Nwabuoku, Udoka Shalom; Okwuribo, Promise; Kpangban, Aghogho; Odokuma, Igho Emmanuel (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Turmeric (Curcuma Longa) is a rhizomatous, perennial plant, flowering in nature, belonging to the ginger family. It’s potential therapeutic benefits, has led to an increase in its consumption globally. Despite severe studies on turmeric there is still existing literature gap on the effect of turmeric on the kidney. This study espoused the potential nephrotoxic sequel of the kidney following exposure to turmeric extract in adult wistar rats. Methods Ethical approval for the study was obtained from the Ethics and Research Committee in the Faculty of Basic Medical Sciences of the Delta State University, Abraka. 24 adult female Wistar rats, weighing between 180g - 200g were used as experimental model. They were grouped into 4 groups (A, B, C and D), and were euthanized at the end of the experimental days and effect of tumeric extract were studied. Results We found that tumeric extract effect on the kidney histology was unremarkable in all groups with varying doses. Also observed was moderate significant increase in creatinine and urea level in treated groups when compared with control group. Conclusions Obtained upshot suggests that oral administration of turmeric with graded doses and time dependent showed no microscopic or cytoarchitectural changes, but with a negative functional report.